2013
DOI: 10.1016/j.jiph.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Premarital Screening and Genetic Counseling program: Knowledge, attitude, and satisfaction of attendees of governmental outpatient clinics in Jeddah

Abstract: Knowledge in the general population about the PMSGC program was low. Implementation of school and university educational campaigns is important. Improved counseling and adding new topics for counseling on genetic, chronic, and psychiatric problems; building healthy families; reproduction and fertility are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 27 publications
6
43
0
5
Order By: Relevance
“…Another study reported that nearly one third of the participants' source of information on PMS was media 20 . Another study The most common source of knowledge was TV 21,22 . In a study of India it has been noted that the most common sources of information regarding thalassemia were health care professionals and electronic media i.e.…”
Section: Fig 2: Awareness About Thalassemia Prevention (N=130) 4 Discmentioning
confidence: 99%
“…Another study reported that nearly one third of the participants' source of information on PMS was media 20 . Another study The most common source of knowledge was TV 21,22 . In a study of India it has been noted that the most common sources of information regarding thalassemia were health care professionals and electronic media i.e.…”
Section: Fig 2: Awareness About Thalassemia Prevention (N=130) 4 Discmentioning
confidence: 99%
“…Of those at-risk couples who underwent premarital testing in Saudi Arabia, Ibrahim et al found that 40% subsequently cancelled their marriage plans. 11 In contrast, Al-Farsi et al found that 14.8% of surveyed Omanis would marry even if they found out their future spouse was a carrier; moreover, 37.5% stated that they would not be willing to change their decision to marry based on premarital screening results. 10 However, this issue could potentially be solved by increasing awareness of the importance of premarital screening and the consequences of passing on hereditary blood disorders.…”
Section: Mandating Premarital Carrier Screeningmentioning
confidence: 95%
“…11 Al-Farsi et al also suggested unifying counselling and educational efforts in order to develop protocols to standardise clinical practice at primary healthcare centres and encourage knowledge and awareness of premarital screening among Omani patients. 10 This recommendation might help to increase the effectiveness of the current premarital screening programme.…”
mentioning
confidence: 99%
“…Previous findings regarding the high prevalence and uneven distribution of sickle cell disease in Saudi Arabia are supported by community based studies conducted by Al-Qurashi et al (2008), and more recently by Al-Suwaid et al (2015). What may be concluded therefore is that a high prevalence of genetic haemoglobin disorders has persisted in Saudi Arabia (Ibrahim et al, 2013;.…”
Section: Prevalence Of Sickle Cell Disorder In Saudi Arabia 23mentioning
confidence: 82%
“…More recently, it has been argued that a lack of knowledge still exists among Saudi parents with children with chronic illness and disability (Gharaibeh, 2009). It has also been established that knowledge among the Saudi population regarding premarital screening and genetic counselling programs remains poor (Ibrahim et al, 2013).…”
Section: 1mentioning
confidence: 99%